The Origins of the Science of Canon Law: Gratian and the Inartificiosa Eloquentia - Viejo-Ximénez, José Miguel (Studia canonica, 2014)
The author links the structure of the Second Part of the Concordia discordantium canonum with Gratian’s methods of harmonization. While the material of the First and the Third Part were put in order at a later stage, the causes were present in the primitive conception of the work, belonging to the writing project. The first glosses and comments of the decretists explained this rhetorical category. From this data it is possible to appreciate the intellectual atmosphere in which Gratian was trained and educated, the original nucleus of his book, and the links between civil lawyers, theologians and canonists at the beginnings of the twelfth century Renaissance.